Diagnostic Accuracy of Aortic Root Cross‐sectional Area/Height Ratio in Children and Young Adults with Marfan and Loeys‐Dietz Syndrome. (11th November 2015) - Mariucci, Elisabetta; Donti, Andrea; Guidarini, Marta; Oppido, Guido; Angeli, Emanuela; Lovato, Luigi; Wischmeijer, Anita; Finlay, Malcolm; Gargiulo, Gaetano D.; Picchio, Fernando M.; Bonvicini, Marco
ABSTRACT: Background: Accurate quantification of aortic dilatation is critical in children with syndromes associated with thoracic aortic aneurysm, yet classification of normality is difficult. Current methods of normalization use body surface area to account for growth, despite a nonlinear relationship of body surface area to aortic root dimensions. In contrast, height has a linear relationship with aortic root dimensions in normal children, is simple to measure and requires no secondary calculation. We evaluated the diagnostic accuracy of an height‐based aortic root‐indexing method, aortic root cross‐sectional area/height ratio (AHr), in children with Marfan and Loeys‐Dietz syndromes. Methods: A cohort of 54 children with Marfan or Loeys‐Dietz syndromes, aged 3 months to 17 years, were evaluated with a transthoracic echocardiogram. AHr was measured in diastole at sinuses of Valsalva (SoV) and proximal ascending aorta (pAA) in a group of normal subjects matched for age and body surface area and normal values were provided. AHr values were recorded for patients and compared with z ‐scores results obtained with Gautier's and Campens's nomograms. Results: AHr values in the group of normal subjects were 2.6 ± 0.6 at SoV and 2 ± 0.5 at pAA. Categorization of z ‐scores and AHr showed good correspondence between AHr and Gautier's method ( P  = .341 at SoV and .185 at pAA) and AHr and Campens method ( P =.465 at SoV and 0.110 at pAA). Conclusions: There was a good correspondence of AHr results with two different z ‐scores. AHr is a simple to use and valid option to quantify aortic root dilatation in pediatric patients.